Serrated Polyps and Serrated Polyposis Syndrome - Ashburn, Jean H.; Plesec, Thomas P.; Kalady, Matthew F. (Clinics in Colon and Rectal Surgery, 2016)
Colorectal serrated polyps are intermediate lesions in the serrated neoplastic pathway, which account for up to 30% of colorectal cancers. This pathway is biologically distinct from the adenoma-to-carcinoma sequence, with associated cancers exhibiting mutations in the BRAF oncogene, DNA promoter hypermethylation, and microsatellite instability. An evolving understanding of these unique lesions has led to the development of a more accurate classification, improved endoscopic identification, and tailored clinical management guidelines. This article reviews serrated polyps and serrated polyposis syndrome.
Keywords: serrated polyps; sessile serrated adenoma/polyp; serrated neoplasia; serrated polyposis